(untitled) - Finder, Joseph (New York, 2020)
"In New York Times bestselling author Joseph Finder's new thriller, private investigator Nick Heller is hired to infiltrate a powerful family whose wealth and reputation hide something far more sinister"--
Library Journal Prepub Alert
Kirkus Reviews
Publishers Weekly
Booklist
Adult
Keywords: Rich people; Fiction; Mystery fiction; Mystery fiction; Suspense fiction